2004
DOI: 10.1002/ange.200352389
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motion of Endohedral Fullerenes in Single‐Walled Carbon Nanotubes

Abstract: Production and purification of iCeC 82Ce-containing endohedral fullerenes were produced by the so-called reversed arc technique developed by the Nagoya group as described previously. 1 A Ce-doped graphite rod (anode) was kept a few mm apart from a graphite block (cathode) in a vacuum chamber. The rod and the block were connected to an external power supply and high current was passed through them (300 -500 A). The vaporisation took place in He atmosphere (50 -100 Torr). The resulting soot contained 10 -20 % fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Open‐ended carbon nanotubes provide internal cavities (1–2 nm in diameter) that are capable of accommodating organic molecules and biomolecules of respective sizes. For example, it has been shown that open SWCNTs can accommodate fullerenes56 and small proteins such as cytochrome c inside their internal cavities, leading to the stable immobilization of the proteins in bioactive conformations 57. DNA could also enter into the carbon nanotube cavities, and DNA transport through a single MWCNT channel has been directly followed by fluorescence microscopy 58.…”
Section: Functionalization Of Carbon Nanotubes With Biomoleculesmentioning
confidence: 99%
“…Open‐ended carbon nanotubes provide internal cavities (1–2 nm in diameter) that are capable of accommodating organic molecules and biomolecules of respective sizes. For example, it has been shown that open SWCNTs can accommodate fullerenes56 and small proteins such as cytochrome c inside their internal cavities, leading to the stable immobilization of the proteins in bioactive conformations 57. DNA could also enter into the carbon nanotube cavities, and DNA transport through a single MWCNT channel has been directly followed by fluorescence microscopy 58.…”
Section: Functionalization Of Carbon Nanotubes With Biomoleculesmentioning
confidence: 99%
“…(288 kJ mol À1 ) for C 60 and a single-walled carbon nanotube (SWNT), [6] and can be higher for larger fullerene cages. Previously, we [5,7,8] and others [9,10] have exploited the unique affinity of nanotubes to absorb fullerenes with metals inside leading to (M@C n )@SWNT structures in an exceptionally high yield (up to 100 %), in which metal atoms are arranged in a perfect chain along the nanotube channel (Figure 1 b).…”
Section: Introductionmentioning
confidence: 99%
“…[12] This reduction process also explains why the silver nanoparticles were not observed in the initial SEM study: the silver nanoparticles are enclosed inside the VO x matrix giving an inorganic Ag-in-VO x peapod (c.f. organic carbon nanotube systems), [13] which is stable under SEM conditions, in which the sample is also coated by gold through sputtering. This observation is further verified by the high mechanical stability of the silver nanoparticle/vanadium oxide interface.…”
Section: Methodsmentioning
confidence: 99%